2008
DOI: 10.1093/molbev/msn079
|View full text |Cite
|
Sign up to set email alerts
|

Selection on Amino Acid Substitutions in Arabidopsis

Abstract: Studies of nucleotide diversity have found an excess of low-frequency amino acid polymorphisms segregating in Arabidopsis thaliana, suggesting a predominance of weak purifying selection acting on amino acid polymorphism in this inbreeding species. Here, we investigate levels of diversity and divergence at synonymous and nonsynonymous sites in 6 circumpolar populations of the outbreeding Arabidopsis lyrata and compare these results with A. thaliana, to test for differences in mutation and selection parameters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 46 publications
8
68
1
Order By: Relevance
“…Excess rare polymorphisms and higher r pd for nonsynonymous compared to synonymous variation appear to be general patterns in viral (Edwards et al 2006;Pybus et al 2006;Hughes 2009) and bacterial genomes (Hughes 2005;Charlesworth and Eyre-Walker 2006;Rocha et al 2006;Hughes et al 2008) as well as in animal mtDNA (Ballard and Kreitman 1994;Nachman et al 1996;Rand and Kann 1996;Hasegawa et al 1998;Wise et al 1998;Weinreich and Rand 2000;Gerber et al 2001;Subramanian et al 2009). Similar patterns have been noted in nuclear genes from yeast (Doniger et al 2008;Liti et al 2009), Drosophila (Akashi 1996;Fay et al 2002;Loewe et al 2006;Andolfatto et al 2011), humans (Cargill et al 1999;Sunyaev et al 2000;Hughes et al 2003;Williamson et al 2005;Boyko et al 2008;Keightley and Halligan 2011;Subramanian 2012), mice (Halligan et al 2010), and plants (Bustamante et al 2002;Nordborg et al 2005;Foxe et al 2008;Fujimoto et al 2008;Gossmann et al 2010;Branca et al 2011;. Excess rare polymorphism could reflect very strongly deleterious mutations if the number of sampled chromosomes is very high, but sample sizes in most of these studies do not approach such levels.…”
Section: Within-lineage Contrasts Of Polymorphism and Divergencementioning
confidence: 55%
“…Excess rare polymorphisms and higher r pd for nonsynonymous compared to synonymous variation appear to be general patterns in viral (Edwards et al 2006;Pybus et al 2006;Hughes 2009) and bacterial genomes (Hughes 2005;Charlesworth and Eyre-Walker 2006;Rocha et al 2006;Hughes et al 2008) as well as in animal mtDNA (Ballard and Kreitman 1994;Nachman et al 1996;Rand and Kann 1996;Hasegawa et al 1998;Wise et al 1998;Weinreich and Rand 2000;Gerber et al 2001;Subramanian et al 2009). Similar patterns have been noted in nuclear genes from yeast (Doniger et al 2008;Liti et al 2009), Drosophila (Akashi 1996;Fay et al 2002;Loewe et al 2006;Andolfatto et al 2011), humans (Cargill et al 1999;Sunyaev et al 2000;Hughes et al 2003;Williamson et al 2005;Boyko et al 2008;Keightley and Halligan 2011;Subramanian 2012), mice (Halligan et al 2010), and plants (Bustamante et al 2002;Nordborg et al 2005;Foxe et al 2008;Fujimoto et al 2008;Gossmann et al 2010;Branca et al 2011;. Excess rare polymorphism could reflect very strongly deleterious mutations if the number of sampled chromosomes is very high, but sample sizes in most of these studies do not approach such levels.…”
Section: Within-lineage Contrasts Of Polymorphism and Divergencementioning
confidence: 55%
“…Our estimates of N e s (Ă€30 for the additive model in A. arenosa; -10 in A. lyrata) in fact suggest stronger purifying selection in A. arenosa than in A. lyrata, potentially reflecting a larger long-term effective population size, as suggested by comparisons of levels of nucleotide diversity in this study with previous estimates in A. lyrata. Interestingly, patterns of polymorphism at nonsynonymous compared to synonymous sites in the orthologous genes from these two species also follow this trend; from the analysis of these same orthologous loci in A. lyrata by Foxe and colleagues ( Foxe et al 2008), the ratio of numbers of nonsynonymous (164) to synonymous (212) polymorphic sites is significantly elevated compared with the ratio in A. arenosa (176 vs. 323; Fisher's exact test, P , 0.05). Taken together, this suggests that the increased effective size in the autotetraploid species dominates over any relaxation of selection associated with masking of deleterious recessive mutations.…”
Section: Discussionmentioning
confidence: 84%
“…We did MK tests to assess the significance of any differences in fixation of either slightly deleterious or advantageous mutations, by comparing the ratios of replacement to synonymous changes between sites diverged between A. lyrata and A. thaliana, and polymorphic within A. lyrata [supplemental Table 1 shows the results for the pericentromere region loci and loci from chromosomes AL6 and AL7; the AL1 and AL2 arm locus data are published in Foxe et al (2008) and are not shown here]. No significant differences were observed between the low-and high-diversity centromeres, and there were no significant MK test results for any individual pericentromere region loci, or in pooled data for each centromere.…”
Section: Resultsmentioning
confidence: 99%